(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: An extensive epidemiological investigation was applied regarding the risk factors, to a cohort of patients with pre‐existing heart disease, hospitalized for tertiary prophylaxis in a rehabilitation hospital. The group of 499 patients from all regions of the country respected the proportions of gender and environment of origin for the general population of Romania and was adjusted according to regional proportions. The ranking of risk factors and protection factors present in the studied population was made, at the level of each of the 8 regions of the country and for the whole country consolidated. The profile of the cardiovascular patient was identified. We used risk factors for population characterization, not for aggregation into tools for assessing total cardiovascular risk (as is the trend in large cohort studies since Framingham) The data processing was done to be able to develop prevention strategies in the interest of the specific individual, not to standardize population characteristics and translate them to the individual thus decreasing their appropriateness. Keywords: 1 cardiovascular risk‐factors, 2 cardiovascular diseases prevention , 3 cardiovascular rehabilita‐tion